Strategi Dakwah KH. Lanre Said: Studi atas Buku Jejak Dakwah KH. Lanre Said Ulama Pejuang dari DI/TII hingga Era Reformasi - Abdul Havid, Ilham; Haif, Abu (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
The method of da'wah represents a systematic approach to delivering religious material to achieve specific objectives. The implementation of da'wah activities requires appropriate and effective strategies. The process of conveying the message of da'wah must be conducted accurately and relevantly to the intended audience. The legal basis for da'wah has been established in the Qur'an and Hadith. Referring to Surah An-Nahl verse 125 of the Qur'an, Muslims are not only commanded to carry out da'wah but are also provided guidelines regarding the methodology of its implementation. This verse outlines that da'wah should be conducted in a wise manner and in harmony with the principles of religious teachings. This research examines the da'wah strategy of KH. Lanre Said, a prominent Islamic figure and preacher in Sulawesi, based on the book "JEJAK DAKWAH KH. LANRE SAID Ulama Pejuang dari DI/TII hingga Era Reformasi" (The Da'wah Trail of KH. LANRE SAID: A Warrior Scholar from DI/TII to the Reformation Era). This study employs a library research method with a qualitative approach. Data is collected through observation, documentation, and interviews, with the researcher as the primary instrument. The research focuses on KH. Lanre Said's da'wah journey from the Dutch colonial period to the establishment of his Islamic boarding school. The researcher's tasks include determining the research focus, selecting informants, collecting data, evaluating data quality, analyzing, interpreting, and drawing conclusions based on findings. The approach used is a qualitative method, where data is processed in the form of verbal descriptions. The aim is to present the research results clearly and comprehensively, both for the researcher and readers, and to avoid ambiguity in understanding the research findings.